Tailoring the ground state of the ferrimagnet La2Ni(Ni1/3Sb2/3)O6 - Franco, Diego Gaspar (2013)
We report on the magnetic and structural properties of La2Ni(Ni1/3Sb2/3)O6 in polycrystal, single crystal and thin film samples. We found that this material is a ferrimagnet (Tc≈100 K) which possesses a very distinctive and uncommon feature in its virgin curve of the hysteresis loops. We observe that bellow 20 K it lies outside the hysteresis cycle, and this feature was found to be an indication of a microscopically irreversible process possibly involving the interplay of competing antiferromagnetic interactions that hinder the initial movement of domain walls. This initial magnetic state is overcome by applying a temperature dependent characteristic field. Above this field, an isothermal magnetic demagnetization of the samples yield a ground state different from the initial thermally demagnetized one.